Preoperative Carbohydrate Loading in Elective Surgery A Narrative Review - Godyń-Müller , Kacper; Brzeziński, Michał; Zeigner, Martin; Błaszczyk, Joanna; Grześkowiak, Michał; Kasprzak, Mateusz; Kulak, Bartosz; Pelant, Hanna; Majchrzak, Zuzanna; Pierzyńska, Klaudia (Journal of Education, Health and Sport, 2026)
Preoperative fasting has been a cornerstone of anesthetic practice for decades, yet prolonged nil-by-mouth regimens exacerbate perioperative insulin resistance, amplify the surgical stress response, and worsen patient comfort. Preoperative oral carbohydrate loading has been incorporated into Enhanced Recovery After Surgery (ERAS) protocols as a strategy to maintain a fed-like metabolic state before elective surgery, yet clinical evidence is heterogeneous, effect sizes on hard endpoints are modest, and key questions on optimal timing, dosing, and suitability in high-risk subgroups remain unresolved. This review critically appraises the effects of preoperative carbohydrate drinks on perioperative metabolic outcomes, patient-centered comfort, clinical recovery endpoints, and safety across multiple surgical specialties.